Mg/Zn metal‐air primary batteries using silk fibroin‐ionic liquid polymer electrolytes. Issue 1 (16th November 2022) - Haskew, Mathew J.; Nikman, Shahin; O'Sullivan, Carys E.; Galeb, Hanaa A.; Halcovitch, Nathan R.; Hardy, John G.; Murphy, Samuel T.
Abstract: Batteries are utilized in a multitude of devices encountered in our daily lives. Here we describe a comparative study of Magnesium‐air and Zinc‐air primary batteries using silk fibroin‐ionic liquid polymer electrolytes (composed of Bombyx mori silk fibroin and choline nitrate). The ionic conductivity of the films was of the order of mS cm −1 which is sufficient to satisfy the conductivity requirements for many battery applications, the open circuit voltages (V) for the Mg 1:1 SF:IL and 1:3 SF:IL batteries just after fabrication were ca. 1.8 and 1.7 V, respectively; the 1:1 SF:IL battery had a capacity of 0.84 mAh cm −2, whereas the 1:3 SF:IL battery had a capacity of 0.68 mAh cm −2 . The open circuit voltages (V) for the Zn 1:1 SF:IL and 1:3 SF:IL batteries were in the range of 1.3 and 1.2 V just after fabrication; the 1:3 SF:IL battery displayed a capacity of 0.96 mAh cm −2 and the 1:3 SF:IL battery displayed a capacity of 0.72 mAh cm −2 . Integration of the PE and substitution of the carbon cloth electrodes with degradable materials would offer routes to production of transient primary batteries helping to address the global issue of electronic waste (e‐waste). Abstract : Energy storage materials have broad applicability in technical and medical applications. The metal‐air primary batteries described herein display properties meeting the requirements for many battery applications, and after substitution of the non‐degradable cathode may be useful in helping solve the global e‐waste problem.